2020
DOI: 10.2486/indhealth.2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

Work-related post-traumatic stress disorder: report of five cases

Abstract: Post-traumatic stress disorder (PTSD) may arise after events involving a risk to physical integrity or to life, one’s own or that of others. It is characterized by intrusive symptoms, avoidance behaviors, and hyper-excitability. Outside certain categories (e.g., military and police), the syndrome is rarely described in the occupational setting. We report here five unusual cases of work-related PTSD, diagnosed with an interdisciplinary protocol (occupational health visit, psychiatric interview, psychological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…16 Despite survival and healing, post-traumatic stress disorders like unsociable personalities, avoidance behaviours, and hyperexcitability have been observed increasingly among post-burned patients. 17 The prevalence and type of work-related burns (WRB) and their clinical characteristics are dissimilar in different societies and work environments. Various factors such as social, economic, cultural level, occupational settings, safety regulations, industry characteristics, and lifestyle affect it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Despite survival and healing, post-traumatic stress disorders like unsociable personalities, avoidance behaviours, and hyperexcitability have been observed increasingly among post-burned patients. 17 The prevalence and type of work-related burns (WRB) and their clinical characteristics are dissimilar in different societies and work environments. Various factors such as social, economic, cultural level, occupational settings, safety regulations, industry characteristics, and lifestyle affect it.…”
Section: Introductionmentioning
confidence: 99%
“…Those who return to work might also experience difficulties reintegrating into the workplace 16 . Despite survival and healing, post‐traumatic stress disorders like unsociable personalities, avoidance behaviours, and hyperexcitability have been observed increasingly among post‐burned patients 17 …”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) refers to a condition where an individual suffers hyper-arousal, re-experiencing of an event, difficulty falling asleep, nightmares, intrusive recollections and avoidance following exposure to an event that involved death or serious injury or a threat to others. 1,2 Commonly found in military personnel, it has been defined in the Diagnostic and Statistical Manual of Mental Disorders Fifth edition (DSM-5) of the American Psychiatric Association, with one of the triggering events being repeated or extreme exposure to aversive details of a traumatic event. 3 The latter perfectly encapsulates the standard work of a forensic pathologist in regularly going to scenes where there have been one or more violent deaths, helping to identify and collect human remains, photographing and describing injuries and traumatic lesions in detail, dissecting sometimes fragmented, decapitated or decomposed bodies in the mortuary, generating a detailed description of the findings, and then spending time in court describing the mechanism and degree of suffering, while often having professional credibility attacked by examining lawyers.…”
mentioning
confidence: 99%
“…4 Despite this, it has been stated that in health workers, other than emergency and intensive care units, PTSD is 'rarely observed'. 2 Certainly, this profile may have been altered by the current coronavirus disease 2019 pandemic. 5 A study of crime scene investigators in the USA, however, found the incidence of PTSD to be twice that of the general American population.…”
mentioning
confidence: 99%